Civic Participation-Element of European Democracy - Ana-Maria Bercu (CES Working Papers, 2009)
Democracy is explained by giving the power to the government, with the consent of citizens, expressing their will, directly or indirectly through voting. Promoting and respecting individual and collective rights and freedoms is the foundation of democracy. Citizen participation is remarkable on two levels in the European government: one, as a citizen of European Union member state, in which exercises the rights and freedoms, the second as a European citizen (in agreement with the Treaty of Maastricht in 1993) which has claimed rights and freedoms recognized by law. Citizens of EU Member States elect, directly or indirectly, representatives (national) in the Community institutions to represent their interests.
Keywords: 330; democracy; individual liberties; individual rights; European governance; fundamentals rights; European Constitution; European Citizen